Germination responses of native fire ephemerals of Patagonian grasslands to smoke water and karrikinolide - Gonzalez, Sofía; Franzese, Jorgelina; Ghermandi, Luciana (Frontiers in Plant Science, 2025)
Plant fire ephemerals are well-adapted to fire-prone environments, with germination strategies linked to fire-related cues like smoke. Germination requirements linked to fire cues in Patagonian fire ephemerals are poorly studied, with no research on the effects of smoke water (SW) and smoke isolated karrikinolide (KAR) on their germination. We assessed the germination responses of two native ephemeral herbs, Boopis gracilis, and Nicotiana linearis, to SW and KAR1 at three concentrations (1/100, 1/1000, and 1/10000) and a Control (no SW or KAR1). Seeds collected on different harvest dates were incubated in a germination chamber, and germination responses were analyzed using Generalized Linear Models and Kaplan-Meier survival curves. KAR1 significantly enhanced and accelerated germination in both species, with the strongest effect at the highest concentration (1/100). In contrast, SW did not stimulate germination and inhibited germination in N. linearis at the highest concentration. This inhibitory effect decreased with storage time, suggesting that toxic compounds in SW degrade over time. Additionally, N. linearis seeds exhibited variable germination across harvest years, likely due to after-ripening requirements. Our findings highlight the contrasting effects of SW and KAR1 on seed germination; KAR1 being a reliable germination stimulant. The chemical complexity of smoke water (heterogeneous composition and uncertain concentration) and the time elapsed since its production likely limit its efficacy in promoting germination. These results provide valuable insights into post-fire seedling dynamics in Patagonian grasslands for the conservation in fire-affected ecosystems.